Association of APOE genotype with CT markers of cerebral amyloid angiopathy in spontaneous intracerebral haemorrhage - Feng Gao; Lu Tang; Dongsheng Fan; Nan Li; Xu Huang; Xiaolu Liu; Qiong Yang; Xiangzhu Zeng; Kailin Xia (Stroke and Vascular Neurology)
Background and objective We investigated the association of APOE alleles with CT-based cerebral amyloid angiopathy (CAA) markers including subarachnoid extension (SAE) and finger-like projection (FLP).Methods We included patients with acute primary supratentorial intracerebral haemorrhage (ICH) from a multicentre cohort in China. First, the association of APOE with ICH location (lobar vs non-lobar) was evaluated. Next, the relationships of APOE with SAE, FLP, and the coexistence of the two (SAE+FLP) were evaluated.Results 533 patients with supratentorial ICH were enrolled. Among them were 138 patients with lobar ICH and 395 with non-lobar ICH. Compared with the non-lobar group, APOE ε4 (OR 1.894, 95% CI 1.138 to 3.154, p=0.014) and ε2/ε4 (OR 6.098, 95% CI 1.414 to 26.293, p=0.015) were associated with lobar ICH. With regard to CAA markers, APOE ε2 was associated with SAE (OR 2.109, 95% CI 1.167 to 3.810, p=0.013), ε4 was associated with FLP and SAE+FLP (OR 3.026, 95% CI 1.353 to 6.767, p=0.007; OR 3.514, 95% CI 1.485 to 8.316, p=0.004, respectively) and ε2/ε4 was associated with all three factors (SAH: OR 7.599, 95% CI 1.764 to 32.734, p=0.006; FLP: OR 20.333, 95% CI 3.278 to 126.137, p=0.001; SAE+FLP: OR 30.568, 95% CI 4.460 to 209.503, p<0.001) after adjusting for age, and remained significant after adjusting for age and ICH volume.Conclusion In patients with spontaneous supratentorial ICH, APOE ε2 and ε4 alleles were associated with SAE and FLP, respectively, suggesting APOE allele-specific effects on CT markers of CAA and their potential mechanisms.